EFEKTIVITAS EKSTRAK NIMBA DALAM PENGENDALIAN ULAT GRAYAK (Spodoptera litura F.) PADA TANAMAN SELADA - Alfian Rusdy (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2009)
Effectiveness of Neem Extract in Controlling Armyworm (Spodoptera Litura F.) in Lettuce Alfian Rusdy Fakultas Pertanian Unsyiah, Darussalam Banda Aceh ABSTRACT Research objectives were to evaluate effectiveness of seed and leaf neem extracts at various concentrations in controlling armyworm in lettuce. Experimental design used was factorial completely randomized design, consisting of eight combinations of treatment with three replications. Factors examined were firstly neem extract of seed and leaf and secondly concentration of the neem extracts, which consists of four levels for each of the 5%, 10%, 15% and 20%. Variables observed were mortality, percentage of pupa, percentage of imago, and intensity of damaged plants. Results showed that use of seed and leaf extracts of neem plant can control armyworm (Spodoptera litura F.) in lettuce plants. Seed extract was more toxic than leaf extract of neem. The most effective concentration was 20 cc/100 ml solution (20%), followed by 15 cc (15%), 10 cc (10%), and 5 cc (5%).